Sex-based differences in the genomic response, innate immunity, organ dysfunction, and clinical outcomes after severe blunt traumatic injury and hemorrhagic shock. Issue 3 (September 2016) - Lopez, Maria-Cecilia; Efron, Philip A.; Ozrazgat-Baslanti, Tezcan; Zhang, Jianyi; Cuschieri, Joseph; Maier, Ronald V.; Minei, Joseph P.; Baker, Henry V.; Moore, Frederick A.; Moldawer, Lyle L.; Brakenridge, Scott C.
Abstract : INTRODUCTION: The effect of sex on posttraumatic pathophysiology and outcomes after severe traumatic injury remains debated. We sought to determine the relationship of sex to the genomic and inflammatory responses, and clinical outcomes after hemorrhagic shock. METHODS: We analyzed blunt trauma patients in hemorrhagic shock from a prospective multi-institutional cohort study to assess for sex-based differences in the genomic response and clinical outcomes. Serially drawn blood samples were analyzed to evaluate peripheral leukocyte genomewide expression and circulating inflammatory mediators at intervals between 0.5 and 28 days after injury. Multivariate logistic regression models were developed to assess the effect of sex on outcomes after controlling for age, injury and shock severity, blood transfusion, and comorbidities. RESULTS: The cohort consisted of 1, 285 (67%) male and 643 (33%) female blunt trauma patients. Injury and shock severity were similar between the two groups. There were small but statistically significant differences between males and females regarding their age, body mass index, and 12-hour blood and crystalloid administration. Organ failure was more severe in males, with slower recovery (9.0 vs. 6.5 days) in males compared to females ( p < 0.01). However, there were no differences between males and females in plasma levels of IL-6, IL-8, IL-10, IL-1β, tumor necrosis factor alpha, and monocyte chemoattractant protein 1. Multivariate analysis revealed that sex was not a significant independent risk factor for complicated recovery or 28-day mortality. Transcriptomic analysis revealed 333 genes with significant differential expression patterns between males and females (FDR, <0.001), including genes associated with general inflammation, innate immunity, cell adhesion, and cell signaling. None of the former genes were directly associated with sex hormones or X/Y chromosomes. CONCLUSION: There are sex-specific differences in the leukocyte genomic response to severe injury that are associated with more robust and longer-duration organ dysfunction. However, these expression patterns do not seem to be associated with sex-linked genes or circulating cytokine level differences, and do not translate to worsened sex-specific organ failure outcomes or inpatient mortality. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.